2015
DOI: 10.1155/2015/913260
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Nickel Chloride Doped PMMA Films

Abstract: Films of PMMA and PMMA doped with NiCl 2 with different contents were prepared using the casting technique. The optical properties of all films were investigated using spectrophotometric measurements of absorbance and transmittance in the wavelength range 200-800 nm. The change of the calculated values of the optical energy gaps with increasing NiCl 2 content has been interpreted in terms of the structural modifications of the PMMA matrix. The optical energy gap decreased from 3.6 to 3.05 eV with increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…Similar to the studies in the literature, the indirect transition energies ( E i ) were obtained lower than the direct transition energies ( E d ) . In literature, the studies on various PMMA composites have reported that the optical band gap energy is in the range of 3.0–5.5 eV for pure PMMA , and the band gap energy level of insulating materials is around 6 eV. As pure PMMA is an insulating polymer, the value of 6 eV obtained is an acceptable result.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to the studies in the literature, the indirect transition energies ( E i ) were obtained lower than the direct transition energies ( E d ) . In literature, the studies on various PMMA composites have reported that the optical band gap energy is in the range of 3.0–5.5 eV for pure PMMA , and the band gap energy level of insulating materials is around 6 eV. As pure PMMA is an insulating polymer, the value of 6 eV obtained is an acceptable result.…”
Section: Resultssupporting
confidence: 80%
“…This behavior was attributed to the increase of the local levels in the band gap, hence the distant between the conduction and valance band was decreased . This is an expected result, because the conductive additives added to the insulating PMMA matrix increase the conductivity of the composites and composites become semi‐conductive state . Additionally, E d values have two distinct linear regions in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…However, by increasing the content of PEG in the PVA/PEG blend, the skin depth showed an obvious decrease in its values due to an increase in the absorption possibility. Consequently, we can conclude that skin depth was transmittance related [16].…”
Section: Skin Depthmentioning
confidence: 78%
“…Skin depth δ is also known as the penetration depth and it describes the distance that an electromagnetic wave can penetrate into a polymeric material. The skin depth was estimated as a function of wavelength by using the following relation [16]:…”
Section: Skin Depthmentioning
confidence: 99%
“…After doped the average oscillator position values decreased and with increasing doping concentration to 5wt%, the average oscillator strength increased with impurity percentage as shown in Table 1. The skin depth x could be calculated using the following relation [18]: x = λ / 2πk (5) Where k is the extinction coefficient. Figure 6 shows the variation of skin depth as a function of wavelength for all films.…”
Section: Resultsmentioning
confidence: 99%